(untitled) (Latakia University Journal -Basic Sciences Series, 2016)
In this work, we have found exact traveling wave solutions for generalized Fitzhug-Nagumo equation with arbitrary constant coefficients, by using the homogeneous balance method, The obtained results shows that these solutions changes with the specials solution of Ricati ODE with arbitrary constant coefficients , and shows that this method is simple, direct and very efficient for solving this kind of nonlinear PDEs, It can be applied to nonlinear PDEs which frequently arise in engineering sciences, mathematical physics and other scientific real-time applications fields. نقوم في هذا العمل بإيجاد حلول تامة ذات موجة جوالة (Traveling wave solutions)، لمعادلة Fitzhugh-Nagumo المعممة ذات الأمثال الثابتة الكيفية باستخدام طريقة تعويض موازنة التجانس مع معادلة ريكاتي التفاضلية العادية ذات الأمثال الثابتة. وتبين النتائج التي حصلنا عليها أنه كلما تغير الحل الخاص لمعادلة ريكاتي نحصل على حل جديد للمعادلة التفاضلية الجزئية المعطاة، كما يتبين أن هذه الطريقة بسيطة وفعالة لهذا النوع من المعادلات التفاضلية الجزئية غير الخطية، ويمكن أن تطبق على معادلات تفاضلية جزئية غير خطية أخرى وبخاصة التي تأتي من علوم الهندسة والفيزياء الرياضية ومجالات علمية تطبيقية أخرى.